Two RNA editing sites with cis-acting elements of moderate sequence identity are recognized by an identical site-recognition protein in tobacco chloroplasts - Kobayashi, Yusuke (Oxford University Press, 2008)
The chloroplast genome of higher plants contains 20–40 C-to-U RNA editing sites, whose number and locations are diversified among plant species. Biochemical analyses using in vitro RNA editing systems with chloroplast extracts have suggested that there is one-to-one recognition between proteinous site recognition factors and their respective RNA editing sites, but their rigidness and generality are still unsettled. In this study, we addressed this question with the aid of an in vitro RNA editing system from tobacco chloroplast extracts and with UV-crosslinking experiments. We found that the ndhB-9 and ndhF-1 editing sites of tobacco chloroplast transcripts are both bound by the site-specific trans-acting factors of 95 kDa. Cross-competition experiments between ndhB-9 and ndhF-1 RNAs demonstrated that the 95 kDa proteins specifically binding to the ndhB-9 and ndhF-1 sites are the identical protein. The binding regions of the 95 kDa protein on the ndhB-9 and ndhF-1 transcripts showed 60% identity in nucleotide sequence. This is the first biochemical demonstration that a site recognition factor of chloroplast RNA editing recognizes plural sites. On the basis of this finding, we discuss how plant organellar RNA editing sites have diverged during evolution.